Mediation Concepts to Foster Collaboration and Satisfaction within different Office Environments - Koestler, Tina; Orel, Marko, 1986-; Staněk, Ondřej; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
Abstract:Digital transformation and the sharing economy have changed the way we work and consequently contributed to the rise of a phenomenon called coworking. Virtual team members, freelancers, and entrepreneurs escape the isolation of working remotely and become coworkers by joining a community in which friendships, collaboration, knowledge- and resource sharing are fundamental to the satisfaction of individuals involved in this form of microcluster. The majority of coworking spaces celebrate the diversity of their member portfolio. This study explores the trend of the contrary business model that is coworking specializing in a niche market or business segment connecting individuals who share similar backgrounds and values. The comparison of a sample of heterogeneous and homogeneous coworking spaces has found that the outcomes of successful collaboration between coworkers reach beyond friendships to actual business transactions independent of the type of business model. However, informal interaction and intellectual stimulation are found to be the most important drivers to engage in networking activities which is why a gatekeeping process to ensure stronger synergies among members are found not desirable by coworkers. Generally, homogeneous coworking spaces differ their members into those actively involved in the community by learning and giving or receiving feedback and those merely sharing the office facilities. Whereas in heterogenous coworking, individuals voluntarily chose the intensity of their involvement with the community.
Vedoucí práce: Marko Orel
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses